Challenges for the Westphalian Statehood in the Twenty First Century - Sidra Pervez; Sadia Khanum, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
The Treaty of Westphalia is a major hallmark of the modern history of nations. It not only covers the Europeans but also encompasses the foreign policies and diplomatic conduct of all the modern nation states. Over the centuries, nations followed the Westphalian peace model to run the international system/order smoothly. However, with the rise of globalization in 20th century, the changing political and economic landscape posing challenges to the Westphalian narrative once again. The questions on the validity of the Westphalian model of state sovereignty have initiated a debate on the expected new World Order long ago. How states could deal with the globalization related challenges facing the state sovereignty and supreme authority in decision making is yet to be answered. This paper is a descriptive study to understand the challenges to the old system in the Globalization related World Order of 20th and 21st century.